Respuesta :
Simplifying
-2x + -4y = 9
Solving
-2x + -4y = 9
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4y' to each side of the equation.
-2x + -4y + 4y = 9 + 4y
Combine like terms: -4y + 4y = 0
-2x + 0 = 9 + 4y
-2x = 9 + 4y
Divide each side by '-2'.
x = -4.5 + -2y
Simplifying x = -4.5 + -2y13/18
169
-11
5x - 5y = 7
169
-11
5x - 5y = 7
Simplifying -2x + -4y = 9 Solving -2x + -4y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -2x + -4y + 4y = 9 + 4y Combine like terms: -4y + 4y = 0 -2x + 0 = 9 + 4y -2x = 9 + 4y Divide each side by '-2'. x = -4.5 + -2y Simplifying x = -4.5 + -2y13/18
169
-11
5x - 5y = 7
Read more on Brainly.com - https://brainly.com/question/1639237#readmore